Letter from Carl D. Duncan to Patricia Whiting, February 20, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan mentions acquiring camping equipment for Whiting and comments on the health of Whiting's mother.